Kemiskinan Trans-Gender: Kritik Materialis Atas Identitas, Tubuh dan Produksi Gender Dalam Kapitalisme Neoliberal: Transgender Poverty: A Materialist Critique of Identity, the Body, and the Production of Gender in Neoliberal Capitalism - Mukmin, Muhammad Andry (Jurnal Filsafat Indonesia, 2025)
This study examines the discourse of transsexuality in contemporary biomedicine through the lens of dual reality and situated ontology. By positioning the trans body as a field of tension between biological facts and symbolic meanings, the article rejects both medical essentialism and extreme relativism that dominate gender discourse. The research employs a qualitative-philosophical method, using Nicholas Rescher’s aporetic framework as a reflective tool to process epistemic tensions among science, identity, and power. Within this framework, contradictions are not regarded as problems to be solved but as spaces for critical and ethical reflection. The analysis involves a critical reading of the works of Butler, Foucault, Beauvoir, Haraway, and Preciado, while proposing a reflective compromise that transcends the cis/trans and male/female binaries. The trans body is understood not merely as an effect of power but as a site of resistance and ethical responsibility toward the Other. This study asserts that the liberation of identity does not lie in affirming fixed categories but in openness to ambiguity, negotiation, and transformation as the very core of human existence.